Does the Healthy Body Image program improve lifestyle habits among high school students? A randomized controlled trial with 12-month follow-up. Issue 3 (October 2020) - Sundgot-Borgen, Christine; Friborg, Oddgeir; Kolle, Elin; Torstveit, Monica K.; Sundgot-Borgen, Jorunn; Engen, Kethe M. E.; Rosenvinge, Jan H.; Pettersen, Gunn; Bratland-Sanda, Solfrid
Objectives: Positive embodiment and healthy lifestyle habits seem to be related; therefore, stimulating positive embodiment should promote healthy lifestyle habits. In the current study, we delivered the Healthy Body Image (HBI) intervention among Norwegian high school students and examined the effects on healthy lifestyle habits. Methods: The HBI intervention comprises three interactive workshops, with three overarching themes related to body image, social media literacy, and lifestyle. A total of 2446 boys (43%) and girls in grade 12 (mean age 16.8 years) from 30 high schools participated in this cluster-randomized controlled study. Schools were randomized to the HBI intervention or control study arm. Data on physical activity, eating habits, and sleep were collected at baseline, post intervention, and 3- and 12-month follow-up and analyzed using linear mixed regression models. Results: The intervention had a minor negative effect on physical activity levels in boys at 12-month follow-up and short-term small-to-moderate positive effects on consumption of breakfast and fruit and vegetables, and sleep duration on school days. Conclusions: In future, the lack of satisfactorily long-term effects might be better addressed using a combination of cognitive and behavioral approaches to more optimally integrate positive embodiment and lifestyle changes in the daily life of adolescents. Trial registration: ClinicalTrials.gov ID: PRSNCT02901457. Approved by the Regional Committee for Medical and Health Research Ethics.